The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1161/circulationaha.111.018259
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Torcetrapib on Glucose, Insulin, and Hemoglobin A 1c in Subjects in the Investigation of Lipid Level Management to Understand its Impact in Atherosclerotic Events (ILLUMINATE) Trial

Abstract: Background-High-density lipoproteins have antidiabetic properties in vitro. Furthermore, elevated high-density lipoprotein levels accompanying a genetic deficiency of cholesteryl ester transfer protein are associated with decreased levels of plasma glucose. We now investigate effects on glucose homeostasis of inhibiting cholesteryl ester transfer protein with torcetrapib. Methods and Results-A post hoc analysis of the Investigation of Lipid Level Management to Understand its Impact in Atherosclerotic Events (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
100
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(111 citation statements)
references
References 21 publications
(23 reference statements)
9
100
1
1
Order By: Relevance
“…Therapeutic interventions that increase plasma HDL levels improve glycaemic control in patients with type 2 diabetes [2,3], and treatment with HDL or apoA-I has been shown to increase glucose uptake into skeletal muscle [4,5] and adipose tissue [6]. Furthermore, treatment with HDL or apoA-I increases insulin secretion and production in isolated pancreatic islets and insulinoma beta cell lines [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic interventions that increase plasma HDL levels improve glycaemic control in patients with type 2 diabetes [2,3], and treatment with HDL or apoA-I has been shown to increase glucose uptake into skeletal muscle [4,5] and adipose tissue [6]. Furthermore, treatment with HDL or apoA-I increases insulin secretion and production in isolated pancreatic islets and insulinoma beta cell lines [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In another trial, torcetrapib, a plasma lipid transfer protein inhibitor that also raised HDLC levels, improved glycemic control [27]. In a recent observational study, irrespective of the possible limitations of the study design, patients with hypercholesterolemia appeared less likely to develop T2D than unaffected relatives, suggesting a link between LDL receptor-mediated transmembrane cholesterol transport and T2D [36].…”
Section: Discussionmentioning
confidence: 99%
“…Although increasing plasma HDLC levels have been suggested to reduce the risk of T2D [25], a recent trial showed that treatment with niacin, which raised HDLC, also raised blood glucose and T2D risk [26]. In another trial, treatment with torcetrapib, a plasma lipid transfer protein inhibitor which also raised HDLC concentrations, improved glycemic control [27], but the role of HDLC in reducing the risk of T2D remains poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…Островитянова, 1; тел. : +7(967)24406461; e-mail: babinzevajana@ mail.ru существенным и независимым образом связан с повышенным риском развития ИБС [5,6]. Отрицательная корреляция концен-трации ХС ЛПВП с показателями риска развития ССЗ привела к созданию методов лечения ССЗ при помощи повышения уровня ХС ЛПВП.…”
Section: терапевтический архив 9 2016unclassified